A State of Peace in Europe West Germany and the CSCE, 1966-1975 - Hakkarainen, Petri (Berghahn Books, 2011)
From the mid-1960s to the mid-1970s West German foreign policy underwent substantial transformations: from bilateral to multilateral, from reactive to proactive. The Conference on Security and Cooperation in Europe (CSCE) was an ideal setting for this evolution, enabling the Federal Republic to take the lead early on in Western preparations for the conference and to play a decisive role in the actual East-West negotiations leading to the Helsinki Final Act of 1975. Based on extensive original research of recently released documents, spanning more than fifteen archives in eight countries, this study is a substantial contribution to scholarly discussions on the history of détente, the CSCE and West German foreign policy. The author stresses the importance of looking beyond the bipolarity of the Cold War decades and emphasizes the interconnectedness of European integration and European détente.